The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jhazmat.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of time-dependent fixation of UVI on biochar

Abstract: Biochar, a by-product from the production of biofuel and syngas by gasification, was tested as a material for adsorption and fixation of U VI from aqueous solutions. A batch experiment was conducted to study the factors that influence the adsorption and timedependent fixation on biochar at 20 o C, including pH, initial concentration of U VI and contact time. Uranium (U VI ) adsorption was highly dependent on pH but adsorption on biochar was high over a wide range of pH values, from 4.5 to 9.0, and adsorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…(2) Inner surface complexes were formed by interaction of U( vi ) and biochar, with complex surface coordination and precipitation being the main mechanisms governing the adsorption of U( vi ) over BC and MBC. Thus, the dissolution PO 4 3− and UO 2 2+ contributed to form coordination and oversaturate conditions; 40 (3) the ionic strength of NO 3 − and PO 4 3− influenced the activity coefficient of Pb( ii ) to a higher extent as compared to U( vi ), thereby limiting the transfer of Pb( ii ) on the biochar surface. The optimum anion strengths of NO 3 − and PO 4 3− were 0.01 mol L −1 for Pb( ii ) and 0.04 mol L −1 for U( vi ), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Inner surface complexes were formed by interaction of U( vi ) and biochar, with complex surface coordination and precipitation being the main mechanisms governing the adsorption of U( vi ) over BC and MBC. Thus, the dissolution PO 4 3− and UO 2 2+ contributed to form coordination and oversaturate conditions; 40 (3) the ionic strength of NO 3 − and PO 4 3− influenced the activity coefficient of Pb( ii ) to a higher extent as compared to U( vi ), thereby limiting the transfer of Pb( ii ) on the biochar surface. The optimum anion strengths of NO 3 − and PO 4 3− were 0.01 mol L −1 for Pb( ii ) and 0.04 mol L −1 for U( vi ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the adsorption rate of Pb( ii ) on BC was higher than that on MBC, thereby revealing that Pb( ii ) was physically adsorbed on the biochar, while U( vi ) was preferably adsorbed via chemisorption processes on MBC owing to the higher number of functional groups of this material. 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that biochar exhibits a strong affinity to adsorb U­(VI). However, these studies only present bulk U­(VI) metal adsorption data, which do not provide molecular-scale insights into the coordination of aqueous uranyl species adsorbed to the biochar surface, and, therefore, they cannot be used to calculate intrinsic stability constants of U­(VI)–biochar surface complexes. Since U­(VI) has a complex aqueous speciation, especially in the presence of the common calcium (Ca 2+ ), carbonate (CO 3 2– ), and hydroxyl (OH – ) ions in natural waters, it is critical to consider changes in aqueous speciation when performing adsorption modeling. …”
Section: Introductionmentioning
confidence: 99%
“…Recovery of uranium from seawater has attracted great interest as a hot research topic recently, because of the heavy demand for uranium used in nuclear reactors1234. In seawater, the total amount of uranium is about 4.5 billion tons, one thousand times more than the amount found in mineral ores on land56.…”
mentioning
confidence: 99%